Left ventricular dysfunction in ADPKD and effects of octreotide-LAR: A cross-sectional and longitudinal substudy of the ALADIN trial. (15th January 2019) - Spinelli, Letizia; Pisani, Antonio; Giugliano, Giuseppe; Trimarco, Bruno; Riccio, Eleonora; Visciano, Bianca; Remuzzi, Giuseppe; Ruggenenti, Piero; ,
Abstract: Background and aim: In autosomal dominant polycystic kidney disease (ADPKD) cardiac abnormalities have been observed before the onset of hypertension or renal dysfunction. We sought to characterize, in ADPKD patients, left ventricular (LV) function and its changes after somatostatin-analogue octreotide-LAR treatment. Methods: In a 1:1:1 cross-sectional study, we evaluated LV function by speckle-tracking echocardiography in 34 ADPKD patients from one ALADIN-trial center and in 34 age- and gender-matched healthy controls and 34 equally-matched renal controls with non-cystic chronic kidney disease. Changes in LV function were compared in the 16 and 18 ADPKD patients originally randomized to 3 year-treatment with octreotide-LAR or placebo, respectively. Results: LV twist and untwisting rates were lower in ADPKD patients that in healthy or renal controls (6.1 ± 2.6° vs. 11.1 ± 2.1° and 10.2 ± 3.7°; −49.5 ± 18.1°/s vs. −79.8 ± 12.2°/s and −84.3 ± 25.9°/s, respectively, all p  < 0.001). The correlation between LV mass or diastolic BP and untwisting rate was positive in ADPKD patients ( r  = 0.38, p  = 0.025 and r  = 0.44, p  = 0.011, respectively), not significant in healthy controls and negative in renal controls ( r  = −0.38; p  = 0.023 and r  = −0.40, p  = 0.012, respectively. LV untwisting rate improved from −49.9 ± 18.6°/s to −70.3 ± 27.5°/s with octreotide-LAR, but did not change with placebo ( p  = 0.027 for treatment effect). At adjusted linear regression analysis, octreotide-LAR therapy emerged as the only independent predictor of untwisting rate improvement at final visit [beta coefficient −0.504 (95% CI −46.905–−6.367), p  = 0.014]. Conclusions: In ADPKD patients LV function is early impaired. Somatostatin-analogue therapy might help in preventing or ameliorating LV dysfunction in this population. Clinical Trial Registrationhttp://www.clinicaltrials.gov, NCT0030928. Highlights: In ADPKD patients LV function is impaired trough disease-specific mechanisms. Treatment with octreotide-LAR, a somatostatin analogue, is able to preserve LV function in these patients. Indications of somatostatin-analogue therapy might be broadened to cardiovascular risk amelioration.